PERBANDINGAN APLIKASI PUPUK HAYATI VP3 BERSAMA KOMPOS DAN VERMIWASH PADA BERBAGAI KOMPOSISI TERHADAP HASIL PRODUKSI KEDELAI (Glycine max (L) Merr.) DILAPANG - firman aprilianto dwi setiawan; Novi Arfarita; Indiyah Muwarni (AGRONISMA, 2020)
The aims of this research is to determine the effect of the application of VP3 biofertilizers with compost and vermiwash on the production of soybeans and to know the effect of the application of VP3 biofertilizers with compost and vermiwash compared a biofertilizer combined with compost and NPK fertilizer in the production of soybeans planted in the field. This investigation was carried out on dry land located in the residential area of Bumi Asri, Dau district, Malang. In addition to the Basic Laboratory, Faculty of Agriculture, Malang Islamic University, from June to August 2019. The design used was a simple randomized complete design with 8 treatments and it was repeated 3 times. Results showed that treatment of VP3 biofertilizers 100% (TKHA) showed a significant difference in the results of crop production (number of flowers, percentage of flowers to pods, number of pods, number of root nodules, pod weight, seed weight and seed weight of 100 seeds) and weight dried roots, stems, and leaves of soybean plants (Glycine max (L) Merr.).